2006
DOI: 10.1007/s10584-005-9028-8
|View full text |Cite
|
Sign up to set email alerts
|

Overestimated Biomass Carbon Pools of the Northern mid- and High Latitude Forests

Abstract: Abstract. The biomass carbon (C) stock of forests is one of key parameters for the study of regional and global carbon cycles. Literature reviews shows that inventory-based forest C stocks documented for major countries in the middle and high northern latitudes fall within a narrow range of 36-56 Mg C ha −1 with an overall area-weighted mean of 43.6 Mg C ha −1 . These estimates are 0.40 to 0.71 times smaller than those (61-108 Mg C ha −1 ) used in previous analysis of balancing the global carbon budget. A stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 46 publications
4
55
1
1
Order By: Relevance
“…We used various databases for potential carbon stocks in vegetation 4,16,[60][61][62][63] Table 5 shows potential vegetation units and the potential carbon stock values assigned, and Supplementary Tables 8-12 show results from forest site-data studies that explicitly discern natural from managed forests 32,33 . A comparison of these data reveals that the data we use are well in line with the site-specific studies 36,37 . SCpot was then calculated as the arithmetic mean of all three maps for each grid cell.…”
Section: Npp Of the Actual Vegetation (Nppact )supporting
confidence: 75%
See 1 more Smart Citation
“…We used various databases for potential carbon stocks in vegetation 4,16,[60][61][62][63] Table 5 shows potential vegetation units and the potential carbon stock values assigned, and Supplementary Tables 8-12 show results from forest site-data studies that explicitly discern natural from managed forests 32,33 . A comparison of these data reveals that the data we use are well in line with the site-specific studies 36,37 . SCpot was then calculated as the arithmetic mean of all three maps for each grid cell.…”
Section: Npp Of the Actual Vegetation (Nppact )supporting
confidence: 75%
“…61), suggesting that tree height has decisive influence due to tree architecture (height is much larger than diameter). While for temperate and boreal forests, based on sitedata analyses, tree height is found to be a good indicator for carbon stocks at larger scales 36,76 , the interrelation is less straightforward, but still strong, for tropical forests, due to the high structural complexity, species variability, and variations in wood density, stem diameter, and the number of trees per area, as well as due to environmental factors 77,78 . As we use tree-height information only for downscaling national carbon stock data to the grid, rather than to calculate carbon stocks from allometric relationships, the related problems-that is, the heterogeneity of wood density and species 16 -are less important sources of uncertainty in our study.…”
Section: Carbon Stock Of the Actual Vegetation (Scact )mentioning
confidence: 99%
“…Prentice et al (2001) concluded that globally boreal forests contain vast terrestrial carbon stocks, estimated at 395-559 Pg C, 1 compared to tropical and temperate forests with respectively 428-553 and 159-292 Pg C (although other authors have given lower estimates for boreal forests, e.g., Sabine et al (2004), Fang et al (2006)). …”
Section: Background and Knowledge Gapsmentioning
confidence: 99%
“…However, most of these previous studies were mainly conducted on forest biomass C storage at the national and regional scales with different estimation methods and different forest resource data. Moreover, there are few precise studies concerning direct plot investigations for various forest types, C storage estimates that include understory, forest floor, and soil, and the relationship between climatic factors and forest types on regional scales [12][13][14][15][16]. An age-related study on C storage in a black locust forest ecosystem on the Loess Plateau showed that tree C storage increased from 5 to 38 years, but significantly decreased from 38 to 56 years owing to high tree mortality.…”
Section: Introductionmentioning
confidence: 99%